Redefining cell death: ferroptosis as a game-changer in ophthalmology - Wei, Yuan; Lin, Yumeng; Li, Youjiaxi; Liu, Jiaxuan; Yang, Yaqi; Chen, Haoran; Han, Zhongyu; Wang, Ke; Qian, Tao; Ju, Yuan; Zheng, Wei (Frontiers in Immunology, 2025)
Ferroptosis, recently proposed as a novel type of cell death, is characterized by unique characteristics and recognition functions. It is involved in diverse physiological processes and in the onset and progression of various diseases and is characterized by reactions between reactive oxygen species (ROS) and iron-dependent lipid peroxidation. This process is finely regulated by a variety of metabolic pathways. Ferroptosis fundamentally differs from conventional cell death mechanisms such as apoptosis, necrosis, and autophagy. In recent years, research on ferroptosis in the field of ophthalmology has gradually emerged, and a large amount of evidence has shown that it is closely related to the occurrence and development of ophthalmic diseases such as age-related macular degeneration (AMD), diabetic retinopathy (DR), retinal ischemia–reperfusion injury (RIRI), retinitis pigmentosa, dry eye disease, cataracts, and glaucoma. This paper provides a comprehensive review of the latest advancements in ferroptosis within ophthalmological research and systematically describes the molecular mechanisms and pathophysiological significance of ferroptosis in the pathogenesis and progression of ophthalmic diseases. Exploring the mechanisms of ferroptosis holds promise for the delivery of novel molecular targets and therapeutic approaches to prevent and treat ophthalmic diseases. Additionally, its clinical translational and application are anticipated to surmount current therapeutic limitations and emerge as a significant direction for breakthroughs in the precision medicine era.